2013
DOI: 10.2147/cia.s38420
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of citicoline in mild vascular cognitive impairment: the IDEALE study

Abstract: BackgroundThe studio di intervento nel decadimento vascolare lieve (IDEALE study) was an open multicenter Italian study, the aim of which was to assess the effectiveness and safety of oral citicoline in elderly people with mild vascular cognitive impairment.MethodsThe study was performed in 349 patients. The active or citicoline group was composed of 265 patients and included 122 men and 143 women of mean age 79.9 ± 7.8 years selected from six Italian regions. Inclusion criteria were age ≥ 65 years, Mini-Menta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
27
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 17 publications
3
27
0
4
Order By: Relevance
“…Results from this study are consistent with prior research that suggests citicoline may play a role in increasing attention and alertness (Babb et al, 2002; Bruce, 2012; Cotroneo et al, 2013; Silveri et al, 2008). Citicoline is a compound that consists of cytidine and choline.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Results from this study are consistent with prior research that suggests citicoline may play a role in increasing attention and alertness (Babb et al, 2002; Bruce, 2012; Cotroneo et al, 2013; Silveri et al, 2008). Citicoline is a compound that consists of cytidine and choline.…”
Section: Discussionsupporting
confidence: 89%
“…Since PDE has been shown to decrease with age and be associated with cognitive memory loss, increase in this substance may improve overall cognitive skills. In a recent study examining mild cognitive impairment in 349 elderly patients, Cotroneo and colleagues (2013) found that the citicoline group showed improvement in mini mental state examination (MMSE) scores after 9 months, compared to the untreated group that showed significant MMSE declines over the same time period. Other investigators have also found that increases in PDE from citicoline supplements have led to improved memory in older adults (Babb et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recent evidences suggest that citicoline may increase dopamine production and glutamate uptake in the brain to improve cognition [2], [3]. Citicoline could also reduce free fatty acid release and recover the activities of mitochondrial ATPase and membrane Na + /K + ATPase to alleviate brain damage [4], [5].…”
Section: Introductionmentioning
confidence: 99%
“…Итальянское исследование IDEALE. В 2015 г. были опубликованы результаты открытого многоцентрового исследования, проведенного в Италии, -IDEALE [29]. Его особенность -длительный период наблюдения за пациен-тами (9 мес).…”
unclassified